The removal of veterinary antibiotics in the high-rate anaerobic bioreactor: continuous and batch studies. (9th September 2022) - Zeng, Zhuo; Zheng, Ping; Kang, Da; Li, Wenji; Xu, DongDong; Chen, Wenda; Pan, Chao; Guo, Leiyan
Abstract: Veterinary antibiotics in swine wastewater has drawn great public attention. The removal processes of sulfamethizole (SMZ), enrofloxacin (ENR) and chlortetracycline (CTC) were investigated in the high-rate anaerobic process. The continuous experiments demonstrated that in 3 L working volume and with the organic loading rate 5 kg/(m 3 ·d) rised to 20 kg/(m 3 ·d), the average removal efficiencies of the high-rate anaerobic bioreactor for SMZ, ENR and CTC were 0, 54 and 100%, respectively. By using fixed-bed adsorption models, the saturation time of SMZ, ENR and CTC were 4 hydraulic retention time ( HRT ) (24 h), 8 HRT (48 h) and 372 HRT (2, 232 h). In the batch experiments, the adsorption and biodegradation characteristics of anaerobic granular sludge were determined. In the high-rate anaerobic bioreactor, SMZ removal process mainly relied on the adsorption but it was very weak; ENR removal process was based on the adsorption and biodegradation; CTC removal process was based to a large extent on the adsorption because of the big capacity of AnGS. These results were helpful to create a rational basis for designing more suitable treatment systems as feasible barriers to the release of antibiotics into the environment. HIGHLIGHTS: The removal processes and mechanisms of common veterinary antibiotics in the high-rate anaerobic bioreactor were investigated. Anaerobic granular sludge has an excellent chlortetracycline adsorption capacity. Good enrofloxacin removal performance was ascribed to adsorption and biodegradation together. Graphical Abstract